The receptionist robot - Holthaus, Patrick; Wachsmuth, Sven (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
In this demonstration, a humanoid robot interacts with an interlocutor through speech and gestures in order to give directions on a map. The interaction is specifically designed to provide an enhanced user experience by being aware of non-verbal social signals. Therefore, we take spatial communicative cues into account and to react to them accordingly.